2014
DOI: 10.1063/1.4894735
|View full text |Cite
|
Sign up to set email alerts
|

Double-sided Tl2Ba2Ca2Cu3O10 thin films based high temperature superconducting filter operating above 100 K

Abstract: Articles you may be interested inEffect of paramagnetic Mn ion on the superconductivity of Cu0.5Tl0.5Ba2Ca2−xMnxCu3O10−y J. Appl. Phys. 112, 073920 (2012); 10.1063/1.4757405Nonlinear surface impedance of Tl 2 Ba 2 CaCu 2 O 8 thin films as a function of temperature, frequency, and magnetic field

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Tl-based superconducting films are known to have high T c values, such as Tl 2 Ba 2 CaCu 2 O 8 [27] (Tl-2212, T c ∼ 108 K) and Tl 2 Ba 2 Ca 2 Cu 3 O 8 [28] (Tl-2223, T c ∼ 124 K). Although the T c values of Tl-2212 and Tl-2223 are remarkable, few studies on Tl-based BJJs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Tl-based superconducting films are known to have high T c values, such as Tl 2 Ba 2 CaCu 2 O 8 [27] (Tl-2212, T c ∼ 108 K) and Tl 2 Ba 2 Ca 2 Cu 3 O 8 [28] (Tl-2223, T c ∼ 124 K). Although the T c values of Tl-2212 and Tl-2223 are remarkable, few studies on Tl-based BJJs have been reported.…”
Section: Introductionmentioning
confidence: 99%